Breast cancer in adolescents and young adults less than 40Years of age in Nigeria: a retrospective analysis (2022)
Background. Breast cancer among adolescents and young adult (AYA) females aged 15-39 years is associated with different patterns of aggressiveness, as well as psychosocial and economic issues. At present, the burden of breast cancer among this age group is unknown in Nigeria. There is a need to determine the proportion of AYA with breast cancer in Nigeria. This will inform the development of breast cancer care programs appropriate for this age group. Objective. The objective of this study was to highlight the burden of breast cancer with an emphasis on AYAs in Nigeria and its implications. Methods. A retrospective review of data from cancer registries in Nigeria between 2009 and 2016 was carried out. Results. Among AYA females in Nigeria, breast cancer was by far the most common cancer, constituting 50% of all cancers and 51% (2798 of 5469) of all breast cancer cases. IA third (30.8%) of breast cancer cases in all centers studied were AYAs. Conclusion. The high proportion of AYA with breast cancer is an important feature suggesting that urgent actions are required to ensure early detection and improve breast cancer care among this age group.